GW 11: An efficient wheat variety for terminal heat and moisture stress conditions - Agalodiya, A V; Patel, S S; Patel, B N; Yadav, R S; Augustine, N (Journal of Cereal Research, 2011)
Wheat is an important crop worldwide and is grown onabout 210 million hectares with annual production of about648 million metric tons (FAO 2010). The global wheatproduction should be increased 2% annually until 2020to meet future demand with the compromise of globalwarming, end-use quality and newly evolving pathogen andpest populations under reduced water availability as well asunder abrupt climatic conditions (especially heat stresses).About 35 percent of irrigated wheat area in Gujarat state isunder late sown after cotton and paddy facing heat stressat grain filling stage resulting about 16 percent yield loss ascompared to timely sown wheat. Further, North Gujarat andSaurastra regions covering more than 60% wheat area inGujarat which is prone to water scarcity resulted in drasticreduction in wheat productivity. Therefore, SDAU, Vijapurhas developed variety GW 11 having high stable grain yield,better terminal heat tolerance, efficient water utilization,resistance to black & brown rusts and better grain qualityfor Gujarat state.